Challenges of Total Customer Experience (TCX): Measurement Beyond Touch Points - Chatzopoulos, Christos G.; Weber, Marcel (International Journal of Industrial Engineering and Management, 2018)
Customer Experience (CX) is an already known term and is usuallymeasured at one or more “touchpoints”, which aredirect and indirect interactionsbetween acustomer and acompany. Most companies typically use touchpoint measurements as a representation for the Total Customer Experience (TCX). However,one can argue that this representation is inadequate since CXis also determined by what is experienced before, between and after touchpoints, which definesthe whole customer journey.Thispaper discusses the adequacy of TCX measured only through touchpointsandinvestigates the challenges of (a) defining, (b) modelling and measuring, and (c) managing and improvingTCX. First, TCX definition challengesare discussed and anew definition ofTCXis proposed, considering the four phasesthat characterise the wholecustomer journey that areInitiation, Touchpoints, In-between Touchpoints and Finalization. Second, the challenges of modelling and measuring TCXare addressed and a new TCX model that measuresemotions is proposed and explainedthrougha fictitious case example.Third, threechallenges formanaging and improving TCXare discussedanda new way to manage and improve the TCX performance in a company is presented and appliedby using the developed TCX model and the caseexample. Article history: Received (10.10.2018); Revised (21.11.2018); Accepted (05.12.2018)